Drug prescribing patterns at primary health care level and related out-of-pocket expenditures in Tajikistan. Issue 1 (December 2016) - Donadel, Morgane; Karimova, Gulzira; Nabiev, Ruslan; Wyss, Kaspar
Abstract Background The Government of Tajikistan is reforming its health system to make access more equitable. Nonetheless, out-of-pocket expenditures (OPE) remain a key modality for purchasing health care. Drugs remain a major driver of household expenditures for health. We conducted a household survey to investigate drug prescribing patterns at primary health care (PHC) level as well as the related OPE. Methods Adult patients in eight districts who had visited a PHC facility in the period March to May 2014 were interviewed at home, using a structured questionnaire. A descriptive analysis was conducted and regression models were constructed to identify factors influencing the number of drugs provided and the types of drugs prescribed. Results There were 1281 (80.1 %) patients who received a drug prescription after visiting a doctor at PHC level. 16.2 % of them had five or more drugs prescribed concomitantly. The number of drugs prescribed to patients ranged from 0 to 8 and was statistically different across regions (RRS region =3.3; Khatlon region = 3.1;p  = 0.05), after adjusting for age and sex. In 31.1 % of cases, prescriptions included an intra-venous (IV) injection; in 45.6 % of cases, a non-IV injection; in 52.9 % of cases, an antibiotic; and in 61.0 % of cases, vitamins. Patients suffering from a respiratory disease had higher odds of being prescribed an IV injection and antibiotics. Vitamins were widely prescribed across all diseases. In 94.5 % of cases, the patients interviewed procured at least one of the prescribed drugs. Among those who received a prescription, 2.0 % were not able to procure at least one drug due to a lack of money. In 94.9 % of cases, respondents reported purchasing drugs in private pharmacies. Median expenditures for drugs procured following consultation were 45 TS (US$ 6.9) corresponding to 77.6 % of total expenditures related to the visit (58 TS, US$ 8.8). Conclusions In a context where OPE are important, drugs represent an important income source for health service providers. Such a situation does not favour rational prescribing nor efficient service delivery, and is potentially harmful for patients. In particular, the economic ramifications cause high levels of expenditure for patients and households with detrimental, knock-on effects in the more vulnerable segments of the population.